2017
DOI: 10.1007/s00394-017-1415-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations of vitamin D status with dietary intakes and physical activity levels among adults from seven European countries: the Food4Me study

Abstract: The prevalence of vitamin D deficiency varied considerably among European adults. Dietary intakes of ≥10 μg/day of vitamin D from foods and/or supplements and at least 30 min/day of moderate- and vigorous-intensity PA were the minimum thresholds associated with vitamin D sufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 52 publications
(60 reference statements)
3
17
0
1
Order By: Relevance
“…as recently proposed by the Institute of Medicine Dietary Reference Intake Committee. Vitamin D intake is lower in women, which is in line with findings obtained for the participants of the Food4Me study [28]. The prevalence of vitamin D supplementation in Poland is also low, with only 4.4% of women and 2.6% of men reporting regular vitamin D supplementation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…as recently proposed by the Institute of Medicine Dietary Reference Intake Committee. Vitamin D intake is lower in women, which is in line with findings obtained for the participants of the Food4Me study [28]. The prevalence of vitamin D supplementation in Poland is also low, with only 4.4% of women and 2.6% of men reporting regular vitamin D supplementation.…”
Section: Discussionsupporting
confidence: 88%
“…Taking into account that dietary supplements are thought to be the second most effective strategy to counteract vitamin D deficiency, a more intensive promotion of vitamin D supplementation in adequate doses seems of particular importance. A study by Manios et al has revealed that vitamin D intakes of at least 10 μg/day from foods and/or supplements can ensure sufficient 25(OH)D concentrations [28]. Some shortcomings of this paper should be recognized.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The exact sun exposure (duration, use of sunscreen and protective clothing) in this cohort was unknown, and we used physical activity as a proxy. Whilst recognizing its limitations, there is a good evidence that greater physical activity is associated with higher vitamin D status [58]. In summary, all the above factors may have contributed to overestimation of low 25(OH)D in the very old, and, consequently, affected estimation of the precise 25(OH)D concentration ranges where there are association with GS and TUG.…”
Section: Discussionmentioning
confidence: 99%
“…VitD deficiency is often present in older adults due to decreased UV-light exposure and reduced VitD synthesis and metabolism [ 16 ]. Therefore, VitD supplementation is often indicated [ 17 ].…”
Section: Introductionmentioning
confidence: 99%